2019
DOI: 10.1111/faf.12396
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on life history strategies in partially anadromous brown trout (Salmo trutta, Salmonidae)

Abstract: This paper reviews the life history of brown trout and factors influencing decisions to migrate. Decisions that maximize fitness appear dependent on size at age. In partly anadromous populations, individuals that attain maturity at the parr stage typically become freshwater resident. For individual fish, the life history is not genetically fixed and can be modified by the previous growth history and energetic state in early life. This phenotypic plasticity may be influenced by epigenetic modifications of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 304 publications
(537 reference statements)
6
59
2
Order By: Relevance
“…However, the lack of significant effects and the reduced power of these tests does not allow us to draw any firm conclusions about this, but it does suggest that this may be an interesting avenue for further study. It is perhaps not surprising though that we did not find an effect of cross type as the two life-history forms have been reported from the same population (Jonsson 1985) and can even be offspring of the same parents (Nevoux et al 2019). In our common garden study, it is important to realize that the trout were not raised under fully natural conditions where other environmental stressors could have influenced metabolic responses of fish, with repercussions for the decision to migrate.…”
Section: Discussionmentioning
confidence: 69%
“…However, the lack of significant effects and the reduced power of these tests does not allow us to draw any firm conclusions about this, but it does suggest that this may be an interesting avenue for further study. It is perhaps not surprising though that we did not find an effect of cross type as the two life-history forms have been reported from the same population (Jonsson 1985) and can even be offspring of the same parents (Nevoux et al 2019). In our common garden study, it is important to realize that the trout were not raised under fully natural conditions where other environmental stressors could have influenced metabolic responses of fish, with repercussions for the decision to migrate.…”
Section: Discussionmentioning
confidence: 69%
“…Brown trout, Salmo trutta L., is a facultatively anadromous species typically displaying partial migration. Resident and migratory individuals can co‐occur sympatrically and display a wide range of life histories (reviewed by, e.g ., Birnie‐Gauvin et al ., 2019; Nevoux et al ., 2019). It is widely acknowledged that resident trout can also produce migratory offspring and vice versa (Dębowski & Dobosz, 2016; Jonsson, 1982; Jonsson & Jonsson, 2006), but so far this has not been quantified among subadults and adults that have recruited to the feeding areas or returned to spawn.…”
Section: Figurementioning
confidence: 99%
“…Brown trout, Salmo trutta L., is a facultatively anadromous species typically displaying partial migration. Resident and migratory individuals can co-occur sympatrically and display a wide range of life histories (reviewed by, e.g., Birnie-Gauvin et al, 2019;Nevoux et al, 2019).…”
mentioning
confidence: 99%
“…The environmental variables that trigger the physiological and behavioural processes leading to migration are, at least partly, understood for salmonids (Dodson et al, 2013;Ferguson et al, 2019). For example, it has been shown that food availability and temperature are among the main environmental factors triggering facultative migration in brown trout (Nevoux et al, 2019;Peiman et al, 2017). However, it has also been shown that individual condition plays a similarly important role with smaller individuals and individuals in poor condition being more likely to adopt an anadromous life-history tactic (Peiman et al, 2017).…”
Section: Adoption Of Alternative Life-history Strategiesmentioning
confidence: 99%